Do Work Experience, Independence, Auditor Competency, And Time Budget Pressure Matter On Audit Quality? - Meini, Zumratul; Karina, Arni; Digdowiseiso, Kumba; Rini, Nurul Alfisyah (Budapest International Research and Critics University, 2022)
This study aims to identify and analyze the effects of work experience, independence, time budget pressure, and competency on audit quality. Data was collected using a survey method by distributing 52 questionnaires to all auditors working in South Jakarta City. All auditors of Public Accounting Firms (KAP) located in South Jakarta are the population in this study. The data analysis technique used in this research is descriptive statistics, multiple regression test, classical assumption test, hypothesis testing, and coefficient of determination test. The results showed that Work Experience, Competence, and Time Budget Pressure partially affected Audit Quality, while Independence did not affect Audit Quality.